AD, Volume 35, n° 1 & 2, 2010 - Full Issue - Journal System, (Africa Development, 2021)
Contents Public Sphere, Linguistic Sphericules and Discourse Communities in Africa Ambadiang Théophile ...........................1 Rulers against Writers, Writers against Rulers: The Failed Promise of the Public Sphere in Postcolonial Nigerian Fiction Ayo Kehinde ................................ 27 Trans-nationalizing the African Public Sphere: What Role for Trans-border Languages? Barro Maimouna ....................... 55 Negotiating Nation-building and Citizenship through the Truth and Reconciliation Committee's 'Dramatic' Spheres: A Reading of Two Post-apartheid Plays Busuyi Mekusi ......................... 71 The African Public Space of Dangarembga's Neria: A Site for Autochthonous Feminist Agency Kapasula Jessie Kabwila ............... 95 'Up as a Rabbit, Down as a Lion': Socio-economic Determinants of New Idioms of Power - Visual Case Stories from Urban Adamaoua, Cameroon Lisbet Holtedahl ........................117 Towards a New Map of Africa through Rastafari 'Works' Niaah Jahlani ............................177 The Emergence of Public Spheres in Colonial Cameroon: The Case of Palm Wine Drinking Joints as lieux de sociabilité in Bamenda Township Nicodemus Fru Awasom .............. 201